Complex evaluation of clinical and instrumental data for grounding of the tactics of operative treatment in patients with resistant epilepsy forms - E. A. Gokhman; V. I. Guzeva; O. V. Guzeva; V. V. Guzeva; V. R. Kasumov; R. D. Kasumov; A. Yu. Kabanov; A. K. Kuralbaev (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
Frequent epileptic seizures and side effects of drugs have a significant negative impact on the quality of life. The main goal in the treatment of such patients is not only to decrease the number of attacks and their severity, but also to improve social adaptation. Surgical treatment for some forms of pharmacoresistant epilepsy improves prognosis and enhances the quality of life of patients, and the result depends on the duration of the disease. The main task of the preoperative examination is the most accurate localization of the epileptogenic zone. In the case of proximity or the overlapping of the epileptogenic zone with functionally significant parts of the crust, additional surveys to determine the latter are conducted. The survey may be conducted using non-invasive techniques, such as MRI, functional MRI, positron emission tomography (PET), single photon emission computed tomography (SPECT) and extracranial electrical stimulation or invasive direct electrical stimulation of the cortex.